Effect of pods storage and fermentation duration on proanthocyanidins content in Malaysian cocoa beans / Suhaila Mohd Sauid, Rabiatul ‘Adawiyah Mahmun and Khairul Bariah Sulaiman - Mohd Sauid, Suhaila; Mahmun, Rabiatul ‘Adawiyah; Sulaiman, Khairul Bariah (Universiti Teknologi MARA Shah Alam, 2018)
The objective of this research is to evaluate the effect of pods storage and fermentation duration towards proanthocyanidins content in Malaysian cocoa beans. The pods storage duration was varied from 0 to 6 days with two days interval, while the fermentation duration of cocoa beans was varied from day 0 until day 5. The amount of proanthocyanidins extracted from the cocoa beans was determined by using UV spectrophotometric and high performance liquid chromatography (HPLC) analyses. The results showed that the total proanthocyanidins contents in all samples from different pods storage and fermentation duration are varied for both analyses. From the results, it shows that fermentation duration has more significant effect to the proanthocyanidins content in Malaysian cocoa beans as compared to the effect of pod storage duration.